Development of Interactive Mobile Learning Media to Enhance Motivation and Learning Outcomes in Elementary School Students’ Mathematics on Social Arithmetic - Arni, Sarah; T, Ahmad Yani; Warneri, Warneri; Salam, Urai; Ariyati, Eka (Newinera Publisher, 2025)
This study was motivated by the low motivation and learning outcomes of elementary school students in mathematics, particularly in social arithmetic, as well as the limited integration of digital technology in classroom instruction. The research aimed to develop interactive mobile learning (ML) media that is engaging, user-friendly, and aligned with the curriculum to enhance students’ motivation and achievement. The study employed a research and development (R&D) method using the ADDIE model through the stages of analysis, design, development, implementation, and evaluation. Validation by media and content experts ensured technical quality and content accuracy. A quasi-experimental design with a pretest–posttest control group was implemented. The results revealed a significant improvement in the experimental group, with the mean posttest score rising from 40.97 to 72.47, while the control group increased by only 4.99 points. Paired t-test and ANCOVA confirmed these differences, and the motivation questionnaire demonstrated high reliability (Cronbach’s Alpha >0.88). Observations and interviews supported the quantitative findings, showing increased engagement, independence, and teacher–student interaction. The interactive ML media proved effective, feasible, and ready for broader implementation as a digital learning innovation supporting 21st-century educational transformation